Partnerships for Enhanced Engagement in Research (PEER) health: a new programme to facilitate LMIC research capacity - Dr. Callie Raulfs-Wang, PhD; Cameron Bess, PhD; Robert Gasior; Kathleen Handley, PhD; James Herrington, PhD; Elizabeth Higgs, MD; Vesna Kutlesic, PhD; Sybil Phillip, MS; Elizabeth Sharp, PhD; Annica Wayman, PhD (Elsevier, 2014)
Background: The Partnership for Enhanced Engagement in Research (PEER) Health programme, funded by the United States Agency for International Development (USAID), is a new research partnership programme that directly supports researchers from developing countries as Principal Investigators in partnership with collaborators at the US National Institutes of Health (NIH). The goals of this programme are threefold: (1) to advance critical evidence to address crucial health challenges facing LMICs; (2) to support collaboration and build on existing relationships between local public health and research institutions, global health practitioners, host country government, NIH researchers, and USAID Missions and Embassy staff; and (3) to build capacity by supporting researchers in LMICs thereby enabling local solutions to context specific challenges. Methods: More than 180 preproposals from 25 LMICs were submitted to the first PEER Health research solicitation focused on Child Survival. After consultation with USAID Missions to ensure relevance to host country health priorities, about 80 applicants were invited to submit a full proposal. The National Institute of Child Health and Human Development organised a special emphasis panel for the scientific review of PEER Health full proposals to address both scientific merit and research capacity building aspects of the grant proposals, whilst maintaining key elements of the standard NIH peer review model. 40 experienced NIH reviewers, representing a wide variety of scientific disciplines and global public health experience, did the peer review of grants using a novel IT system developed for the PEER Health initiative. The National Academies of Sciences hosted an interagency protocol review to ensure scientific validity and compliance with international human subject guidelines. Findings: Sixteen diverse grant partnerships were awarded in ten USAID Child Survival priority countries in Africa and Asia. Research funded under this programme is varied and includes studies from diverse topical areas, including malaria, neonatal sepsis, breast-feeding, tuberculosis, prevention of mother-to-child transmission, among others. Studies include investigation of both facility and community level interventions. NIH partners are largely US based and half are support by the National Institute of Allergy and Infectious Disease (NIAID). Interpretation: Broad interest in this novel programme and applications from 25 countries show a crucial need for more directed funding for research strengthening and partnerships with LMIC Principal Investigators. Funding: USAID, in-kind support from NIH.